Effect of E-Filing Quality and Tax Services on Taxpayer Compliance, Moderated by Compliance Costs - Huda, Rofiul; Daulay, Pardamean; Rulandari, Novianita (Manunggal Halim Jaya, 2026)
Low taxpayer compliance in Indonesia, evidenced by a tax-to-GDP ratio of only 12.1% in 2022, presents a significant challenge despite the implementation of the e-filing system aimed at improving tax reporting efficiency. This study examines the influence of e-filing system quality and tax service quality on individual taxpayer compliance at the Samarinda Ulu Primary Tax Service Office (KPP Pratama Samarinda Ulu), East Kalimantan—a strategic location with 6.22% economic growth in Q1 2024, yet facing an energy transition that affects tax revenues—with compliance cost as a moderating variable. Utilizing a quantitative approach, data were collected from 100 taxpayers through Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. Validity was assessed using factor loadings (>0.70), AVEs (>0.50), and Cronbach's Alpha (>0.70), while varying questionnaire formats controlled standard-method bias. The results show that e-filing system quality does not significantly influence compliance, whereas tax service quality has a significant positive effect. Compliance cost does not moderate either relationship. These findings underscore the importance of enhancing service quality, particularly responsiveness and empathy, to drive compliance. At the same time, improvements to the e-filing system are necessary to address technical issues in Samarinda. Managerial implications suggest team member training and system optimization to support national tax reform.